The Concept of Collective Knowledge in President AS 'Speeches (2000-2025): A Social Epistemological Perspective - Sembiring, Elita Modesta Br; Manugeren, M; Barus, Efendi (Journal of English Language and Education, 2025)
This study examines the concept of collective knowledge in President A.S.’s speeches through the lens of social epistemology, focusing on the period from 2015 to 2020 within the broader temporal frame of 2000–2025. Departing from traditional individualistic accounts of knowledge, the research treats political discourse as a site where knowledge is socially constructed, authorized, and normatively deployed. Presidential speeches are approached not merely as rhetorical instruments but as epistemic practices that shape shared understanding and collective identity. Adopting a qualitative, philosophy-oriented methodology informed by a Systematic Literature Review (SLR) and conceptual discourse analysis, the study analyzes official speeches to identify how collective knowledge is linguistically and philosophically framed. The findings reveal that collective knowledge is articulated through multiple forms, including experiential knowledge grounded in shared social experience, historical knowledge rooted in national memory, and institutional or expert-based knowledge that confers epistemic authority. These forms are strategically mobilized to legitimize political decisions, unify the audience, and guide collective action. From a social epistemological perspective, the study highlights significant tensions between epistemic authority and democratic inclusion. While appeals to collective knowledge foster cohesion and legitimacy, they also risk suppressing epistemic plurality and marginalizing dissenting perspectives. By situating presidential discourse within debates on collective intentionality, epistemic authority, and power, this research contributes to philosophical discussions on the ethical and political dimensions of collective knowing. It demonstrates the relevance of social epistemology for understanding how knowledge functions in contemporary political life.